Association between neighborhood socioeconomic status, built environment and SARS‐CoV‐2 infection among cancer patients treated at a Tertiary Cancer Center in New York City. Issue 2 (28th October 2022) - Dioun, Shayan; Chen, Ling; Hillyer, Grace; Tatonetti, Nicholas P.; May, Benjamin L.; Melamed, Alexander; Wright, Jason D.
Abstract: Background: Racial and ethnic minority groups experience a disproportionate burden of SARS‐CoV‐2 illness and studies suggest that cancer patients are at a particular risk for severe SARS‐CoV‐2 infection. Aims: The objective of this study was examine the association between neighborhood characteristics and SARS‐CoV‐2 infection among patients with cancer. Methods and Results: We performed a cross‐sectional study of New York City residents receiving treatment for cancer at a tertiary cancer center. Patients were linked by their address to data from the US Census Bureau's American Community Survey and to real estate tax data from New York's Department of City Planning. Models were used to both to estimate odds ratios (ORs) per unit increase and to predict probabilities (and 95% CI) of SARS‐CoV2 infection. We identified 2350 New York City residents with cancer receiving treatment. Overall, 214 (9.1%) were infected with SARS‐CoV‐2. In adjusted models, the percentage of Hispanic/Latino population (aOR = 1.01; 95% CI, 1.005–1.02), unemployment rate (aOR = 1.10; 95% CI, 1.05–1.16), poverty rates (aOR = 1.02; 95% CI, 1.0002–1.03), rate of >1 person per room (aOR = 1.04; 95% CI, 1.01–1.07), average household size (aOR = 1.79; 95% CI, 1.23–2.59) and population density (aOR = 1.86; 95% CI, 1.27–2.72) were associated with SARS‐CoV‐2 infection. Conclusion: Among cancer patients in New York City receiving anti‐cancer therapy, SARS‐CoV‐2 infection was associated with neighborhood‐ and building‐level markers of larger household membership, household crowding, and low socioeconomic status. Novelty and impact: We performed a cross‐sectional analysis of residents of New York City receiving treatment for cancer in which we linked subjects to census and real estate date. This linkage is a novel way to examine the neighborhood characteristics that influence SARS‐COV‐2 infection. We found that among patients receiving anti‐cancer therapy, SARS‐CoV‐2 infection was associated with building and neighborhood‐level markers of household crowding, larger household membership, and low socioeconomic status. With ongoing surges of SARS‐CoV‐2 infections, these data may help in the development of interventions to decrease the morbidity and mortality associated with SARS‐CoV‐2 among cancer patients.